2018
DOI: 10.1186/s12870-018-1331-4
|View full text |Cite
|
Sign up to set email alerts
|

A PSTOL-like gene, TaPSTOL, controls a number of agronomically important traits in wheat

Abstract: BackgroundPhosphorus (P) is an essential macronutrient for plant growth, and is required in large quantities by elite varieties of crops to maintain yields. Approximately 70% of global cultivated land suffers from P deficiency, and it has recently been estimated that worldwide P resources will be exhausted by the end of this century, increasing the demand for crops more efficient in their P usage. A greater understanding of how plants are able to maintain yield with lower P inputs is, therefore, highly desirab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 46 publications
3
50
2
1
Order By: Relevance
“…Similarly, for P efficiency, efforts were made to improve P use efficiency in wheat based on the information from rice. Milner et al recently cloned TaPSTOL gene (an orthologous gene of rice PSTOL1) and investigated its effects on wheat under various P supply conditions (Milner et al 2018). They observed that the expression of TaPSTOL was higher in root tips and hairs under limited P supply and the overexpression or silencing significantly impacted agronomic traits.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, for P efficiency, efforts were made to improve P use efficiency in wheat based on the information from rice. Milner et al recently cloned TaPSTOL gene (an orthologous gene of rice PSTOL1) and investigated its effects on wheat under various P supply conditions (Milner et al 2018). They observed that the expression of TaPSTOL was higher in root tips and hairs under limited P supply and the overexpression or silencing significantly impacted agronomic traits.…”
Section: Discussionmentioning
confidence: 99%
“…Transformants were selected as previously described (Perochon et al ., ). For each T0 transformants, the T‐DNA copy number was determined using a qPCR assay (1 copy in lines OE‐1 and OE‐3, 2 copies in line OE‐4 and 3 copies in line OE‐2) as described by (Milner et al ., ) and confirmed for the presence of the transgene insert by PCR amplification of a fragment of TaNACL‐D1 and the NOS (nopaline synthase) terminator (primers listed in Table S1). Plants were grown to the T 4 generation, and at each generation, leaf tissue samples were collected from the overexpression lines to check the presence of T‐DNA and to analyze the segregation ratio to identify homozygous lines.…”
Section: Methodsmentioning
confidence: 99%
“…Relatively few plant orphan genes have been studied in depth. Recent studies revealed that orphan genes are important players in key agronomic traits, including Ms2 that confers male sterility in wheat (Ni et al, 2017), QQS (Qua-Quine Starch) that regulates carbon and nitrogen partitioning across species and TaFROG (Triticum aestivum Fusarium Resistance Orphan Gene) that enhances wheat resistance to disease .…”
Section: Introductionmentioning
confidence: 99%
“…T-DNA copy number was determined using a TaqMan relative quantification (ΔΔCT) assay comparing the relative values of an nptII amplicon to an amplicon of the single copy wheat gene GaMyb within a multiplexed reaction and normalised to a single copy control [ 39 ]. All reactions are carried out using two replicates per plant line.…”
Section: Methodsmentioning
confidence: 99%